Reconsidering the Immiserizing Growth in a Simple Domestic Macroeconomic Model with Financial Assets - Fujita, Yasunori (Archives of Business Research, 2025)
Technological progress does not always lead to increased income or improved well-being. Bhagwati (1958) demonstrated that if a country's exports rise due to technological advances, international prices may fall sharply, potentially reducing overall economic welfare—a phenomenon known as "Immiserizing Growth." Similarly, Prebisch (1950) and Singer (1950) argues that developing countries, which primarily export raw materials, face worsening terms of trade as raw material prices decline over time. Corden and Neary (1982) identified a related issue, "Dutch Disease," where resource booms lead to the decline of other industries, slowing economic growth. This paper extends Fujita (2025) by constructing a macroeconomic model that incorporates financial assets. It shows that technological progress can raise the trading volume of the financial assets while reducing nominal GDP.